Effect of the occupational environment of parents on cryptorchidism. Issue 11 (10th November 2020) - Mitsui, Takahiko; Araki, Atsuko; Miyashita, Chihiro; Ito, Sachiko; Kitta, Takeya; Moriya, Kimihiko; Shinohara, Nobuo; Takeda, Masayuki; Kishi, Reiko; ,
Abstract: Background: The early detection and treatment of cryptorchidism are necessary to preserve male fertility. This study aimed to assess the effect of parents' occupational environment on the incidence of cryptorchidism in their sons. Methods: The study enrolled 51 316 newborn males, whose mothers were recruited in the Japan Environment and Children's Study. We analyzed cryptorchidism incidence in male newborns according to 14 categories of occupation of their parents. We also analyzed the effect of the mother's occupational environment during gestation, including working and night‐shift work, on cryptorchidism incidence. Information on occupations was obtained from self‐administered questionnaires. Cryptorchidism was identified through a survey at birth or 1 month after birth using medical records. Results: Cryptorchidism was identified in 305 male infants (0.59%) at birth or 1 month after birth. Weight, height, head circumference, and chest circumference at birth were significantly lower in male infants with cryptorchidism than in those without the condition. Gestational age was also shorter in mothers whose infants developed cryptorchidism. Moreover, maternal age at delivery and smoking during gestation also had an effect on cryptorchidism incidence. However, multivariate analysis of the 14 categories of occupation of parents during gestation showed no significant effect on cryptorchidism incidence in their male infants. Conclusions: This study revealed that the work environment of parents did not significantly affect the incidence of cryptorchidism in their sons. However, this study might have underestimated mild and transient cases of cryptorchidism. Further studies are necessary to investigate the risk factors of cryptorchidism in relation to parents' occupation.